An Advanced Pharmacy Practice Framework for Australia - Shane Jackson; Grant Martin; Jennifer Bergin; Bronwyn Clark; Ieva Stupans; Gilbert Yeates; Lisa Nissen; Stephen Marty; Paul Gysslink; Andrew Matthews; Sue Kirsa; Kerry Deans; et al. (MDPI AG, 2015)
The need to develop An Advanced Pharmacy Practice Framework for Australia (the "APPF") was identified during the 2010 review of the competency standards for Australian pharmacists. The Advanced Pharmacy Practice Framework Steering Committee, a collaborative profession-wide committee comprised of representatives of ten pharmacy organisations, examined and adapted existing advanced practice frameworks, all of which were found to have been based on the Competency Development and Evaluation Group (CoDEG) Advanced and Consultant Level Framework (the "CoDEG Framework") from the United Kingdom. Its competency standards were also found to align well with the Domains of the National Competency Standards Framework for Pharmacists in Australia (the "National Framework"). Adaptation of the CoDEG Framework created an APPF that is complementary to the National Framework, sufficiently flexible to customise for recognising advanced practice in any area of professional practice and has been approved by the boards/councils of all participating organisations. The primary purpose of the APPF is to assist the development of the profession to meet the changing health care needs of the community. However, it is also a valuable tool for assuring members of the public of the competence of an advanced practice pharmacist and the quality and safety of the services they deliver.